ANALYSIS OF DELIVERY DELAYS USING STATISTICAL PROCESS CONTROL AT 3PL COMPANY - Tarigan, Jenni Br; Hidayatuloh, Syarif; Qisthani, Nabila Noor; Kasanah, Yulinda Uswatun (DAS Institute, 2024)
This study aims to analyze the causes of delivery delays at PT XYZ. Delivery delays have become a critical issue as they can affect customer trust and result in potential losses for the company. The study identifies two main causes of delivery delays: shipping schedules and the aging (storage time) of goods in the warehouse. The method used in this research is Statistical Process Control, which involves several analytical tools such as P-chart, Pareto diagram, fishbone diagram, histogram, and scatter plot. The analysis results show that shipping schedules have a significant impact on delivery delays, with several delivery periods falling outside the upper control limit and lower control limit. Additionally, goods aging exceeding seven days also contribute to delays. Other influencing factors include human aspects (data entry errors), environmental factors (bad weather and changes in shipping schedules), methods (schedule mismatches), and measurements (inaccurate stock data). The study recommends several improvements to enhance delivery efficiency, including optimizing stock recording processes, strengthening work discipline, and improving human resource quality through operational training.